Evolutionary radiation of earless frogs in the Andes: molecular phylogenetics and habitat shifts in high-elevation terrestrial breeding frogs - Rudolf von May; Edgar Lehr; Daniel L. Rabosky (PeerJ, 2018)
The loss of hearing structures and loss of advertisement calls in many terrestrial breeding frogs (Strabomantidae) living at high elevations in South America are common and intriguing phenomena. The Andean frog genus Phrynopus Peters, 1873 has undergone an evolutionary radiation in which most species lack the tympanic membrane and tympanic annulus, yet the phylogenetic relationships among species in this group remain largely unknown. Here, we present an expanded molecular phylogeny of Phrynopus that includes 24 nominal species. Our phylogeny includes Phrynopus peruanus, the type species of the genus, and 10 other species for which genetic data were previously unavailable. We found strong support for monophyly of Phrynopus, and that two nominal species—Phrynopus curator and Phrynopus nicoleae—are junior synonyms of Phrynopus tribulosus. Using X-ray computed tomography (CT) imaging, we demonstrate that the absence of external hearing structures is associated with complete loss of the auditory skeletal elements (columella) in at least one member of the genus. We mapped the tympanum condition on to a species tree to infer whether the loss of hearing structures took place once or multiple times. We also assessed whether tympanum condition, body size, and body shape are associated with the elevational distribution and habitat use. We identified a single evolutionary transition that involved the loss of both the tympanic membrane and tympanic annulus, which in turn is correlated with the absence of advertisement calls. We also identified several species pairs where one species inhabits the Andean grassland and the other montane forest. When accounting for phylogenetic relatedness among species, we detected a significant pattern of increasing body size with increasing elevation. Additionally, species at higher elevations tend to develop shorter limbs, shorter head, and shorter snout than species living at lower elevations. Our findings strongly suggest a link between ecological divergence and morphological diversity of terrestrial breeding frogs living in montane gradients.